Farmer Empowerment in Processing of Shallot Agricultural Products in Sukomoro Municipality, Nganjuk Regency - Noventi, Ike Arni; Mahmudin, M. Nur Kharis (Jurnal Ilmiah Administrasi Publik, 2022)
Nganjuk Regency is one of the areas that has shallot producing centers in East Java. It even ranks 5th out of the top 10 shallot producing regions in Indonesia. Shallot is one of the leading horticultural commodities in Nganjuk Regency and has good prospects for meeting national consumption, a source of income for farmers, and foreign exchange. The problem is, shallot farmers still have low income due to limited access to business services and capital. The purpose of this study is to describe the process and phases of empowering farmers in the Sukomoro Municipality in processing shallot agricultural products as an effort to increase their ability and competitiveness. This research uses descriptive qualitative method. The results showed that the empowerment carried out resulted in the processing of shallot agricultural products in the form of seeds and fried shallot products. The processing is supported by the awareness phase, the transformation phase, and the improvement phase from the farmers. The inhibiting factors are capital and the Covid-19 pandemic, so that protection from stakeholders is needed.